2011
DOI: 10.1016/j.jsb.2010.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of binding of fluorescent, site-specific dansylated amino acids to human serum albumin

Abstract: Human serum albumin (HSA) has two primary binding sites for drug molecules. These sites selectively bind different dansylated amino acid compounds, which—due to their intrinsic fluorescence—have long been used as specific markers for the drug pockets on HSA. We present here the co-crystal structures of HSA in complex with six dansylated amino acids that are specific for either drug site 1 (dansyl-l-asparagine, dansyl-l-arginine, dansyl-l-glutamate) or drug site 2 (dansyl-l-norvaline, dansyl-l-phenylalanine, da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
123
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(134 citation statements)
references
References 37 publications
10
123
0
1
Order By: Relevance
“…34 An identical feature in these two structures is that the sulfonyl groups are close to the positively charged residues (Arg218 and Arg222) of rHSA. However, the location of the dansyl group of DAUDA in the current structure is different from the dansyl group in the rHSADanN structure (PDB 2XVV) 34 [ Fig. 1(D)].…”
Section: Specificity Of Dansylated Compounds As Probes Of Hsa Bindingmentioning
confidence: 95%
See 2 more Smart Citations
“…34 An identical feature in these two structures is that the sulfonyl groups are close to the positively charged residues (Arg218 and Arg222) of rHSA. However, the location of the dansyl group of DAUDA in the current structure is different from the dansyl group in the rHSADanN structure (PDB 2XVV) 34 [ Fig. 1(D)].…”
Section: Specificity Of Dansylated Compounds As Probes Of Hsa Bindingmentioning
confidence: 95%
“…8,9,[30][31][32][33] The binding modes of these dansylated amino acids were largely confirmed by a recent structural study by Curry and coworkers. 34 They showed that ansyl-L-asparagine (DanN), dansyl-L-glutamate (DanE) and dansyl-L-arginine (DanR) with polar or charged amino acid binds to FA7 (Sudlow site I), while dansyl-L-phenylalanine (DanF), dansyl-L-norvaline (DanNV) and dansylsarcosine (DanSRC) with hydrophobic amino acid are specific for FA3/4 (Sudlow site II). 34 An identical feature in these two structures is that the sulfonyl groups are close to the positively charged residues (Arg218 and Arg222) of rHSA.…”
Section: Specificity Of Dansylated Compounds As Probes Of Hsa Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to crystallographic studies ligands such as fatty acids can bind up to seven sites in HSA including both Sudlow´s sites (Carter and Xo, 1994). Site 1 is a large, flexible and multi-chamber cavity within the core of subdomain IIA that comprises all six helices of the subdomain and additional residues from subdomains IB, IIB and IIIA (Ryan et al, 2011). Site 2 in subdomain IIIA is smaller than site 1, and is a largely apolar cavity with well-defined polar features.…”
Section: Introductionmentioning
confidence: 99%
“…One carboxylate makes the salt bridge with Lys199, the second carboxylate is in close vicinity of Arg's 218 and 222 [39]; 2XVW -Dansyl-L-arginine bound to Sudlow site I [39]. The guanidino moiety of the ligand makes the salt bridge with the Glu153, carboxylate of the ligand is in the close vicinity of Arg218.…”
Section: Doi: 105599/admet2228mentioning
confidence: 99%